Studi Empiris Tentang Pegaruh Volume Perdagangan dan Return terhadap Bid-Ask Spread Saham Industri Rokok di Bursa Efek Jakarta Dengan Model Koreksi Kesalahan - Abdul Halim, Nasuhi Hidayat (IAIKAP, 2000)
In US Capital Market, the empirical evident showed that the effet of inventory holding cost of stock on bid-ask spread was positive. This paper attemots to confirm the effect in Indoensian Capital Market. The confirmation is performed by using the error coreection model (ECM). The case in cigarette industry is used in this paper. There are three companies in this industry including PT BAT. PT H.M. Sampoerna and PT Gudang Garam The daily time series data for the year 1996, 1997 and 1998 are used to be analyzed. It was found that the ECM estimation gave the ecident that the transaction volume and/or return negatively effects on bid-ask spread both in term of absolute and relative in cigarette industry. It means that the investory holding cost of stock on bid-ask spread would be postive. Accordingly, the finding is consistent and confirmend.